Cortical Areas Involved in Object, Background, and Object-Background Processing Revealed with Functional Magnetic Resonance Adaptation - Goh, Joshua O. S. (J Neurosci, 2004)
Previous work has suggested that object and place processing are neuroanatomically dissociated in ventral visual areas under conditions of passive viewing. It has also been shown that the hippocampus and parahippocampal gyrus mediate the integration of objects with background scenes in functional imaging studies, but only when encoding or retrieval processes have been directed toward the relevant stimuli. Using functional magnetic resonance adaptation, we demonstrated that object, background scene, and contextual integration of selectively repeated objects and background scenes could be dissociated during the passive viewing of naturalistic pictures involving object-scene pairings. Specifically, bilateral fusiform areas showed adaptation to object repetition, regardless of whether the associated scene was novel or repeated, suggesting sensitivity to object processing. Bilateral parahippocampal regions showed adaptation to background scene repetition, regardless of whether the focal object was novel or repeated, suggesting selectivity for background scene processing. Finally, bilateral parahippocampal regions distinct from those involved in scene processing and the right hippocampus showed adaptation only when the unique pairing of object with background scene was repeated, suggesting that these regions perform binding operations.